Humans as Individual Beings in the Perspectives of Philosophy, Science, and Technology: A Literature Review of Educational Administration - Fetrimen; Nurhasan; Setyorini; Kursih Sulastriningsih; Ulifah Tuljanah (International Journal of Science and Environment (IJSE), 2026)
Human beings as individual entities constitute a fundamental concept in the fields of philosophy, science, and technology, emphasizing the uniqueness, identity, and potential of each individual. This study aims to examine the concept of human beings as individual entities from the perspectives of philosophy, science, and technology, as well as its implications for educational administration. The study employed a qualitative approach using a literature review method (library research) through the analysis of various relevant scholarly sources published between 2018 and 2025. The findings indicate that, from a philosophical perspective, human beings are regarded as entities possessing self-awareness, freedom, and responsibility. From a scientific perspective, humans are understood as biological and psychological beings who develop through interactions with their environment. Meanwhile, from a technological perspective, human beings remain at the center of the educational process despite the rapid advancement of technology. The implications of this study suggest that educational administration should develop systems that are humanistic, adaptive, and responsive to individual needs while integrating technological advancements without neglecting fundamental human values.